The relationship between physical exercise and sense of social fairness among college students: the chain-mediated role of perceived social support and life satisfaction - Sui, Xiaodong; Zhao, Bin; Na, Di; Liu, Jianwu; Zhang, Qi (Frontiers in Psychology, 2024)
Background The development of a stable society is closely linked to a prevalent sense of social fairness. Participating in physical activities, which are inherently social, plays a crucial role in fostering mental stability within social contexts. Objective This study aims to examine how physical exercise influences the sense of social fairness among college students, focusing on the potential mediating effects of perceived social support and life satisfaction. Methods The study surveyed 496 Chinese college students using several scales: the Physical Activity Rating Scale-3 (PARS-3), Perceived Social Support Scale (PSSS), Satisfaction with Life Scale (SWLS), and Social Justice Scale (SJS). Results (1) A positive correlation was found between physical exercise and sense of social fairness (r = 0.151, p < 0.01). A significant direct effect of physical exercise on sense of social fairness was also observed (β = 0.151, t = 3.971, p < 0.01). (2) Physical exercise was a positive predictor of perceived social support (β = 0.113, t = 4.062, p < 0.01), which in turn positively influenced both life satisfaction (β = 0.333, t = 18.047, p < 0.01) and sense of social fairness (β = 0.485, t = 6.931, p < 0.01). Additionally, life satisfaction had a positive effect on sense of social fairness (β = 0.431, t = 3.247, p < 0.01). (3) Both perceived social support and life satisfaction significantly mediated the relationship between physical exercise and sense of social fairness through two pathways: physical exercise → perceived social support → sense of social fairness (mediating effect: 0.055); and physical exercise → perceived social support → life satisfaction → sense of social fairness (mediating effect: 0.016). Conclusion (1) Physical exercise enhances both perceived social support and the sense of social fairness among college students, suggesting that it not only directly contributes to an enhanced sense of social fairness but also fosters supportive social relationships. (2) The influence of physical exercise on the sense of social fairness operates both directly and indirectly through the mediating roles of perceived social support and, sequentially, life satisfaction.